Self-powered photo diodes based on Ga2O3/n-GaAs structures - Kalygina, Vera M.; Kiselyeva, O. S.; Kushnarev, Bogdan O.; Oleinik, Vladimir L.; Petrova, Julianna S.; Tsymbalov, Alexander V. (Semiconductors)
The electrical and photovoltaic characteristics of the Ga2O3/n-GaAs structures have been studied. A gallium oxide film was obtained by HF magnetron sputtering on n-GaAs epitaxial layers with concentration of N_d=9.5·1014 cm-3. The thickness of the oxide film was 120 nm. Measurements at a frequency of 106 Hz have shown that the capacitance-voltage and conductance-voltage dependences are described by curves characteristic of metal-insulator-semiconductor structures and exhibit low sensitivity to radiation with λ=254 nm. When operating on a constant signal, the samples exhibit the properties of a photodiode and are able to work offline. The photoelectric characteristics of the detectors during continuous exposure to radiation with λ=254 nm are determined by the high density of traps at the Ga2O3/GaAs interface and in the oxide film. Keywords: MIS-structures, capacitance-voltage characteristics, volt-siemens characteristics, photocurrent, trap density.